Use of statins for the prevention of cardiovascular disease in 41 low-income and middle-income countries: a cross-sectional study of nationally representative, individual-level data. Issue 3 (March 2022) - Marcus, Maja E; Manne-Goehler, Jennifer; Theilmann, Michaela; Farzadfar, Farshad; Moghaddam, Sahar Saeedi; Keykhaei, Mohammad; Hajebi, Amirali; Tschida, Scott; Lemp, Julia M; Aryal, Krishna K; Dunn, Matthew; Houehanou, Corine; et al.
Summary: Background: In the prevention of cardiovascular disease, a WHO target is that at least 50% of eligible people use statins. Robust evidence is needed to monitor progress towards this target in low-income and middle-income countries (LMICs), where most cardiovascular disease deaths occur. The objectives of this study were to benchmark statin use in LMICs and to investigate country-level and individual-level characteristics associated with statin use. Methods: We did a cross-sectional analysis of pooled, individual-level data from nationally representative health surveys done in 41 LMICs between 2013 and 2019. Our sample consisted of non-pregnant adults aged 40–69 years. We prioritised WHO Stepwise Approach to Surveillance (STEPS) surveys because these are WHO's recommended method for population monitoring of non-communicable disease targets. For countries in which no STEPS survey was available, a systematic search was done to identify other surveys. We included surveys that were done in an LMIC as classified by the World Bank in the survey year; were done in 2013 or later; were nationally representative; had individual-level data available; and asked questions on statin use and previous history of cardiovascular disease. Primary outcomes were the proportion of eligible individuals self-reporting use of statins for the primary and secondary prevention of cardiovascular disease. Eligibility for statin therapy for primary prevention was defined among individuals with a history of diagnosed diabetes or a 10-year cardiovascular disease risk of at least 20%. Eligibility for statin therapy for secondary prevention was defined among individuals with a history of self-reported cardiovascular disease. At the country level, we estimated statin use by per-capita health spending, per-capita income, burden of cardiovascular diseases, and commitment to non-communicable disease policy. At the individual level, we used modified Poisson regression models to assess statin use alongside individual-level characteristics of age, sex, education, and rural versus urban residence. Countries were weighted in proportion to their population size in pooled analyses. Findings: The final pooled sample included 116 449 non-pregnant individuals. 9229 individuals reported a previous history of cardiovascular disease (7·9% [95% CI 7·4–8·3] of the population-weighted sample). Among those without a previous history of cardiovascular disease, 8453 were eligible for a statin for primary prevention of cardiovascular disease (9·7% [95% CI 9·3–10·1] of the population-weighted sample). For primary prevention of cardiovascular disease, statin use was 8·0% (95% CI 6·9–9·3) and for secondary prevention statin use was 21·9% (20·0–24·0). The WHO target that at least 50% of eligible individuals receive statin therapy to prevent cardiovascular disease was achieved by no region or income group. Statin use was less common in countries with lower health spending. At the individual level, there was generally higher statin use among women (primary prevention only, risk ratio [RR] 1·83 [95% CI 1·22–2·76), and individuals who were older (primary prevention, 60–69 years, RR 1·86 [1·04–3·33]; secondary prevention, 50–59 years RR 1·71 [1·35–2·18]; and 60–69 years RR 2·09 [1·65–2·65]), more educated (primary prevention, RR 1·61 [1·09–2·37]; secondary prevention, RR 1·28 [0·97–1·69]), and lived in urban areas (secondary prevention only, RR 0·82 [0·66–1·00]). Interpretation: In a diverse sample of LMICs, statins are used by about one in ten eligible people for the primary prevention of cardiovascular diseases and one in five eligible people for secondary prevention. There is an urgent need to scale up statin use in LMICs to achieve WHO targets. Policies and programmes that facilitate implementation of statins into primary health systems in these settings should be investigated for the future. Funding: National Clinician Scholars Program at the University of Michigan Institute for Healthcare Policy and Innovation, and National Institute of Diabetes and Digestive and Kidney Diseases. Translation: For the Spanish translation of the abstract see Supplementary Materials section.